The Application of Lean Construction uses the Borda Method and the Root Cause Analysis Method (Case Study: Sunrise Mall 2 Construction) - Reza Rahadian; I Putra (Physical Sciences, Life Science and Engineering, 2025)
The construction industry often faces challenges such as delays, cost overruns, and waste. This research aims to improve the efficiency of mall construction projects using lean construction principles. The methods applied include borda method for prioritization, pareto method for identification of the dominant cause of the problem, root cause analysis (RCA) method to analyze the root of the problem and fishbone diagram to visualize the root cause of the problem. The case study was conducted on an ongoing mall construction project. Data were collected through field observations, interviews with relevant parties, and analysis of project documents. The results show that the application of the borda method helps identify the factors that have the most influence on project efficiency, the pareto method focuses attention on 20% of the main causes of problems that contribute 80% to inefficiency, and the RCA method uncovers the underlying root causes. Based on the calculation results, it was found that the most common waste parameter and their sub-parameter were overprocessing with the sub-parameter “Repair”; overproduction with the sub-parameter “Design change”; motion with the sub-parameter “No special storage”; defects with the sub-parameter “Suitability/adequacy of heavy equipment used” waiting with the sub-parameter “Delay in material arrival at project site”.